2011
DOI: 10.1371/journal.pone.0019016
|View full text |Cite
|
Sign up to set email alerts
|

Bordetella pertussis Infection Exacerbates Influenza Virus Infection through Pertussis Toxin-Mediated Suppression of Innate Immunity

Abstract: Pertussis (whooping cough) is frequently complicated by concomitant infections with respiratory viruses. Here we report the effect of Bordetella pertussis infection on subsequent influenza virus (PR8) infection in mouse models and the role of pertussis toxin (PT) in this effect. BALB/c mice infected with a wild-type strain of B. pertussis (WT) and subsequently (up to 14 days later) infected with PR8 had significantly increased pulmonary viral titers, lung pathology and mortality compared to mice similarly infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 90 publications
3
34
1
8
Order By: Relevance
“…Alternatively, bacterial toxins may suppress key components of the anti-viral response such that the pathogenicity of IAV is increased [5]. Recent studies have suggested that the bacterial species that constitute an individual's normal flora represent a key component of the host defence against IAV [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, bacterial toxins may suppress key components of the anti-viral response such that the pathogenicity of IAV is increased [5]. Recent studies have suggested that the bacterial species that constitute an individual's normal flora represent a key component of the host defence against IAV [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Coadministration of PTX also enhanced B. parapertussis infection, and this was found to depend on the presence of alveolar macrophages, but not on the presence of neutrophils. Influenza virus infection in mice is also exacerbated by B. pertussis infection [83]. Prior infection with PTX-producing B. pertussis increased the pulmonary viral load, lung pathology, and mortality compared to mice infected with PTXdeficient B. pertussis.…”
Section: Role Of Ptx In Pathogenesis and Action On Immune Cellsmentioning
confidence: 99%
“…co-infections) with influenza, or develop after influenza infection. It has been shown that the bacteria belonging to the genus Bordetella can be responsible for a potentially severe complication of influenza that can progress rapidly to a serious infection with severe pneumonia (2,20). In pigs, Bbr is involved in the aetiology of atrophic rhinitis, bronchopneumonia, and has been shown to contribute to porcine respiratory disease complex (PRDC) (7).…”
Section: Introductionmentioning
confidence: 99%